Can digital personal assistants persuade people to exercise?. Issue 2 (25th January 2022) - Paay, Jeni; Kjeldskov, Jesper; Papachristos, Elefterios; Hansen, Kathrine Maja; Jørgensen, Tobias; Overgaard, Katrine Leth
ABSTRACT: Digital personal assistants (DPAs) have recently grown in popularity because they are both a commercially available new technology and reasonably affordable to the average household. This opens opportunities for new ways to assist people in everyday activities in their homes through voice-interaction. Physical activity has significant health benefits, and yet globally, 1 in 4 adults are not active enough. To address this, we investigate the persuasive potential of DPAs in increasing people's physical activity at home. We conducted a study with 48 participants to understand the effect of applying three of Fogg's persuasive principles to the design of a DPA exercise programme: Suggestion, Virtual Reward, and Praise. Our findings show that DPAs have the potential, within their current technical and reactive capabilities, to persuade people to increase their physical activity at home, using Suggestion to encourage physical effort, Virtual Reward to encourage endurance, and Praise to create reassurance for beginners. Based on this, we offer three alternate perspectives for developing persuasive DPAs. We also discuss limitations of the study and suggest future research directions around using persuasion with DPAs.